Psychological and Behavior Changes of Consumer Preferences During COVID-19 Pandemic Times: An Application of GLM Regression Model - Ivascu, Larisa; Domil, Aura Emanuela; Artene, Alin Emanuel; Bogdan, Oana; Burcă, Valentin; Pavel, Codruta (Frontiers in Psychology, 2022)
Our life that we consider normal, due to measures taken to limit the spread of the novel coronavirus, was disrupted. The quarantine, isolation, social distancing, and community containment have influenced consumer behavior and contributed to the rapid development of e-commerce. In pandemic times, even those unfamiliar with the online environment have had to adapt and make acquisitions in this new manner. Hence, we focused our research on measuring consumer’s perception of how the restrictive measures imposed to limit the spread of the COVID-19 virus had influenced their decision to buy a product or service from the online environment, given that purchases are highly subjective and influenced by cumulative effects of economic, social, psychological and behavioral factors. Our paper comes with additional insights within the literature. It adds empirical evidence that reveals that the number of transactions and the value per transaction increased during the COVID-19 pandemic and highlights those online purchases will continue so even after the pandemic.